STRATEGI MEDIA RELATIONS DALAM PROGRAM CSR GEOPARK CILETUH: STUDI PT BIO FARMA - Audina, Sheren; Aruman, Akhmad Edhy (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Media relations activity is one of the efforts that can be used to achieve the objectives of the CSR program, which is engaged in the underdeveloped region into an integrated tourism area. This research is expected to provide clear explanation of the media relations strategies conducted by Bio Farma in the CSR program Ciletuh Geopark especially in establishing a good relationship with the media. The research method used is descriptive research with qualitative approach. This research refers to Communicative Action Theory proposed by Jurgen Habermas, Media Relations Theory and CSR Theory. Data collection techniques used in-depth interviews with internal and external sources, the company’s annual reports, literature studies, journals and internet as secondary data. The results show that by doing media relations activities through tiered personalized approach in order to create consensus, good relationships and trust between Bio Farma and journalists. Bio Farma used the basis of claims of validity as a competent resource, especially in establishing relationships with the media.